A Fast Real-Time Calculation Method for SAR Echo History - Xing Chen, Pan Minghai (Hangkong bingqi, 2023)
Aiming at the problem that the simulation calculation of synthetic aperture radar (SAR) target echo is too large, two multi-order Taylor series expansions are used to calculate the distance history in the echo system function, and the fast real-time calculation of the distance history is completed by combining the data extrapolation method. This method uses multiple multiplications and additions instead of square root operation with large amount of calculation, which can ensure the real-time performance of distance calculation under the premi-se of certain calculation accuracy. At the same time, combined with the regularity of distance history model, data extrapolation is used instead of repeated calculation process to further reduce the amount of calculation and improve real-time performance. By comparing the calculation error of different orders of Taylor series expansion at the same distance, the fourth order is the optimal Taylor expansion order under this simulation condition. Finally, the echo simulation and imaging of 9 densely distributed point targets and real scene targets are carried out respectively. The point target simulation results show that the method can reduce the time of generating echo signal by 53 % and increase the speed by 2 times without affecting the performance of echo signal. The real scene simulation results show that the method can be applied to the echo simulation of large scenes.